Lipid-based Nutrient Supplements Prenatal sebagai Tindakan Preventif Terjadinya Berat Badan Lahir Rendah dan Penurunan Fungsi Kognitif pada Bayi - Muhammad Thifan Satyagraha; Rafi Annisa Ulum; Farhan Syafiq Fadhilah (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Stunting in Indonesia is still high. One of the risk factors is the incidence of low birth weight in infants. If not addressed, the quality of human resources in Indonesia will be low. Thus, giving Lipid-based Nutrient Supplements (LNS), which has been carried out by several countries in order to optimize low birth weight and infant cognitive, needs to be researched. This study aims to collect and analyze articles related to the effect of LNS in pregnant women on birth weight and cognitive power in infants. Methods: The design used is a literature review, articles were collected using the Google search engine through several data sources such as Pubmed, Science Direct, Proquest, Ministry of Health, and BPS RI. The criteria for the articles used are research journals with the Randomized Controlled Trial and Systematic Review methods published in 2015 - 2020. Discussion: Based on the articles, the results show that LNS given to pregnant women can increase body mass and increase brain volume in infants. This is caused by the Brain Specific Fatty Acid which includes docosahexaenoic acid (DHA) and arachidonic acid (ARA) which support tissue formation, immunity, and neurodevelopment. Conclusion: Giving LNS to areas where the prevalence of stunting is still high can be a solution to the problem of stunting in these areas. The suggestion from this research is to create an LNS program, especially in areas where the prevalence of stunting is still high.